Assessing the Applicability of Photocatalytic-Concrete Blocks in Reducing the Concentration of Ambient NO2 of Chandigarh, India, Using Box–Behnken Response Surface Design Technique: A Holistic Sustainable Development Approach - Neeru Singla; Sandeep Singla; Parteek Singh Thind; Sandeep Singh; Jasgurpreet Singh Chohan; Raman Kumar; Shubham Sharma; Somnath Chattopadhyaya; Shashi Prakash Dwivedi; Ambuj Saxena; Alibek Issakhov; Nima Khalilpoor (Journal of Chemistry)
Anthropogenic emissions, such as industrial, vehicular, biomass burning, and coal combustion, play a significant role in degrading the atmospheric conditions of India. Therefore, in the present study, applicability of the photocatalytic-concrete blocks was estimated in improving the ambient environment of Chandigarh, India. The photocatalytic-concrete blocks were prepared by mixing the TiO2 particles with cement. All the experiments, designed in accordance with the Box–Behnken approach, in combination with response surface methodology, were performed in a batch reactor. Further, the process parameters, namely, concentration of TiO2 (1 to 5 g), UV-A irradiance (1 to 5 mW/cm2), and relative humidity (RH) (10 to 70%), were optimized to achieve maximum degradation of NO2. Outcomes of batch experiments depicted that the maximum degradation of NO2, that is, 68.32%, was attained at 3.35 g of TiO2, 5 mW/cm2 of UV-A irradiance, and 64.60% RH. The findings of batch experiment were further theoretically applied to degrade the ambient NO2 concentration of Chandigarh, India. It was estimated that using the photocatalytic concrete for construction of Chandigarh’s pavements may reduce the ambient NO2 concentration of Chandigarh, India, to an average of 5.80 μg/m3. Afterwards, reusability of photocatalytic-concrete blocks was also assessed, and it was made evident that after five cycles, their efficiency was reduced by only 7.15%. Subsequently, it was revealed that hydrogen peroxide-based treatment of photocatalytic-concrete blocks could completely regenerate its treatment efficiency. Therefore, it is expected that the findings of this study may prove beneficial in urban planning, as it may assist scientific auditory in identifying the applicability of TiO2-based photocatalysis in mitigating the impacts of vehicular emissions.